Cross Section Translog Production and Elasticity of Substitution in U.S. Manufacturing Industry - Krishnapillai, Sooriyakumar; Thompson, Henry (International Journal of Energy Economics and Policy, 2011)
This paper examines elasticity of substitution among electricity, labor and capital in U.S. manufacturing industry, using cross section data of 2007. In this analysis, Manufacturing industries were categorized into three categories based on input use and technology. Translog homothetic and non-homothetic production functions for each category were estimated but the restrictions imposed for homothetic production were rejected. The estimated parameters of non homothetic production function were used to estimate the own, cross price and Morishma elasticities of inputs for three different manufacturing categories. These elasticities indicate that capital, electricity and labor are substitutes each other. Cross price elasticities indicate that that electricity is weak substitute to capital and labor but capital and labor are strong substitutes to electricity. These elasticities and the availability of nonrenewable energy source suggest that price of electricity or energy will rise faster than wage and interest rate increase with economic growth. This implies that policies promoting the development and commercialization of alternative energy sources would be a better solution than policies promoting new energy saving physical capital or increasing labor productivity to meet the increasing demand for electricity. Keywords: Elasticity of substitution; Manufacturing industries; Translog production function JEL Classifications: D24; L60